The lynch syndrome - a tip of an iceberg: a review of articles - Modi, Birenkumar P. (International Journal of Research in Medical Sciences, 2025)
Lynch syndrome priorly was known as hereditary non-polyposis colorectal cancer (HNPCC), is an autosomal dominant hereditary disorder due to mutation in a mismatch repair (MMR) gene. Individuals with HNPCC are at increased risk for synchronous and metachronous colorectal cancer (CRC). Most common hereditary colorectal carcinoma syndrome (accounts for 2-5% of all colorectal carcinomas) along with 80% of patients develop colorectal carcinoma and also increased risk of endometrial carcinoma (60%), ovarian carcinoma (10-15%) and other cancers including gastric, ovarian, small bowel, urothelial (ureter, renal pelvis, and bladder), prostate, biliary tract, pancreatic, brain (glioblastoma), cutaneous sebaceous neoplasms. Most colorectal cancers are sporadic, but inherited syndromes cause 5% to 10% of cases. Patients with Lynch syndrome tend to develop carcinomas at an earlier age than the general population (average age: 44 years old). The lifetime risk for ovarian cancer in families with Lynch syndrome is ~8%, which is lower than colorectal and endometrial cancers. Molecular profiles at the genetic level indicate that ovarian cancer in Lynch syndrome has a more favorable prognosis than sporadic ovarian cancer. More than half of sporadic ovarian cancers are diagnosed in stage III or IV, but ≥80% of ovarian cancers in Lynch syndrome are diagnosed in stage I or II. This article provides a framework for understanding the etiology of Lynch syndrome, including how to diagnose patients effectively, differentiate somatic from germline causes and how to monitor based on molecular presentation.